DEPICTION OF MEDIEVAL SCOTTISH CULTURE IN DISNEY’S BRAVE - Saprudin Saprudin; Andi Salsabila (Universitas Suryakancana, 2026)
Literature does not merely serve as entertainment but also functions as a medium for delivering messages, meanings, and the author’s experiences and ideas within the context of reality and culture. One such medium is film. This research focuses on the representation of Scottish culture during the medieval era in the film Brave (2012), directed by Brenda Chapman. The study examines traditional cultural symbols as part of the narrative structure and meaning-making process, which also aid in introducing and understanding Scottish culture. The research employs a descriptive qualitative method with an objective approach, analyzing symbols through Perrine’s theory. The data are examined based on the film’s intrinsic elements, particularly symbols related to Scottish culture. The results show that symbols such as the tartan, bagpipe, and festival in Brave not only depict Scottish culture but also reflect values such as clan pride, solidarity, and the conflict between tradition and individual freedom. These symbols also convey moral messages about freedom and destiny. The study concludes that Brave successfully presents Scottish culture by combining traditional elements with social messages that remain relevant to contemporary life.